2019
DOI: 10.31080/aspe.2019.02.0082
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study between Laparoscopic Repair and Open Repair of Pediatric Inguinal Hernia; Outcomes and Benefits

Abstract: Background: The improvement of pediatric laparoscopic instruments and increased experience with laparoscopy technique, laparoscopic inguinal hernia repair in children become an important skill which the laparoscopist must be aware of. Laparoscopic repair of inguinal hernias in children is less invasive, more feasible and less painful. Additionally, this procedure is that, it could allow contra lateral hernia detection and repair in same setting. Aim: In our study we aimed to compare between the outcomes of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…10 Zenitani and partners likewise featured in their investigation that CMIH frequency was lower among patients managed with the LPEC method. 12 The study demonstrated extremely favourable outcomes that in COR gathering, the recurrence rate was 2.7%, while in LPEC gathering, the recurrence rate was just 0.7%. Another investigation led by Zenitani and partners likewise affirmed that a low rate of recurrence was seen in LPEC gathering (0.83%) than COR gathering (2.4%).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…10 Zenitani and partners likewise featured in their investigation that CMIH frequency was lower among patients managed with the LPEC method. 12 The study demonstrated extremely favourable outcomes that in COR gathering, the recurrence rate was 2.7%, while in LPEC gathering, the recurrence rate was just 0.7%. Another investigation led by Zenitani and partners likewise affirmed that a low rate of recurrence was seen in LPEC gathering (0.83%) than COR gathering (2.4%).…”
Section: Discussionmentioning
confidence: 82%
“…3 The findings of a study carried out by Elekiabi and co-workers exhibited different scenarios who reported that mean age in the COR group was 15.14±4.92 months and in the LPEC group was 20.58±3.52 months. 12 Undoubtedly, the study featured that in the two gatherings (COR and LPEC), a large portion of the patients (89.9% in each gathering) were males. The outcome of our investigation is practically similar to an examination directed by Zenitani and partners, who declared that the dominant part (63.3%) of patients were males.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation